Indonesia’s Diplomacy as a Non-Permanent Member of The UN Security Council in Combating to Terrorism Crime 2019-2020 - Yulia Rimapradesi; Taqiyya Rohadatul Aisyi; Ananda Khaerunnisa (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2024)
The United Nations (UN) was formed to maintain world peace and security. The UN gives a mandate to its main body, called the Security Council (SC), to maintain peace and security stability, take necessary actions, and act as a mediator in all issues and conflicts that occur based on the provisions written in the UN Charter. As a member of the UN Security Council, Indonesia is fully committed to maintaining world peace regarding the UN mission. In carrying out its role, Indonesia refers to the free and active foreign policy, the 1945 Constitution, and the UN Charter. This research used qualitative methods to analyze the dynamics of Indonesia's membership in the Security Council in dealing with global issues. The results proved that Indonesia’s policies have tried to fight terrorism crimes through the UN Security Council membership. The mechanisms for conflict resolution put forward an approach to law enforcement, prevention, and the formation of UN Security Council resolutions related to terrorism crimes.